MEKANISME DETEKSI DAN PEMBLOKIRAN KONTEN PERJUDIAN DARING BERBASIS KATA KUNCI MENGGUNAKAN ALGORITMA LEVENSHTEIN DISTANCE - Puji Saputra, Ismail (Jurnal Komputer Terapan, 2025)
Online gambling in Indonesia is increasingly widespread and has negative impacts, both in terms of socio-economic aspects and cybersecurity. One of the methods used by online gambling operators is inserting gambling backlinks into websites, particularly those with .ac.id and .go.id domains, to boost their ranking in search engines. This study aims to develop a keyword-based input detection and blocking mechanism to prevent the insertion of online gambling content into websites. The method employed is Fuzzy Matching with the Levenshtein Distance algorithm, which measures the similarity between user input and gambling-related keywords. The evaluation results show a precision of 1.00, recall of 0.80, F1-score of 0.89, and accuracy of 0.90. These results indicate that the system can detect sentences containing gambling elements with high accuracy; however, false negatives still occur and need further improvement to be minimized. Thus, this mechanism can serve as an initial step in preventing the misuse of websites by cybercriminal groups.